2021
DOI: 10.3389/fmicb.2021.652173
|View full text |Cite
|
Sign up to set email alerts
|

Assessing METland® Design and Performance Through LCA: Techno-Environmental Study With Multifunctional Unit Perspective

Abstract: Conventional wastewater treatment technologies are costly and energy demanding; such issues are especially remarkable when small communities have to clean up their pollutants. In response to these requirements, a new variety of nature-based solution, so-called METland®, has been recently develop by using concepts from Microbial Electrochemical Technologies (MET) to outperform classical constructed wetland regarding wastewater treatment. Thus, the current study evaluates two operation modes (aerobic and aerobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…In the case of Ørby, the organic load from urban wastewater was higher than at IMDEA, but due to seasonal variation, the flow rate was limited to 2 m 3 /day. Both situations revealed organic removal rates lower than other METland studies reported in the literature ( Aguirre-Sierra et al, 2016 ; Prado et al, 2019 ; Ramírez-Vargas et al, 2019 ; Peñacoba-Antona et al, 2021b ). Each system was analyzed independently considering the removal efficiencies based on inlet/outlet concentrations ( Figure 4 ).…”
Section: Resultscontrasting
confidence: 66%
See 1 more Smart Citation
“…In the case of Ørby, the organic load from urban wastewater was higher than at IMDEA, but due to seasonal variation, the flow rate was limited to 2 m 3 /day. Both situations revealed organic removal rates lower than other METland studies reported in the literature ( Aguirre-Sierra et al, 2016 ; Prado et al, 2019 ; Ramírez-Vargas et al, 2019 ; Peñacoba-Antona et al, 2021b ). Each system was analyzed independently considering the removal efficiencies based on inlet/outlet concentrations ( Figure 4 ).…”
Section: Resultscontrasting
confidence: 66%
“…Most recently, Prado et al (2020) reported removals of up to 95% for COD and 71% for TN with the integration of an artificial device, the e-sink, for consuming electrons. These results suggest that the METland system can enhance biodegradation rates, reducing the footprint of classical TWs by 10-fold ( Peñacoba-Antona et al, 2021b ).…”
Section: Introductionmentioning
confidence: 98%
“…5) while achieving COD removal efficiencies of about 90% [35]. A life cycle assessment (LCA) study suggested that they are an environmentally sustainable wastewater treatment technology [88]. Their optimal locations for implementation have been investigated using geospatial tools like multicriteria evaluation and sensitivity analysis [89].…”
Section: Constructed Wetlands With An Electrically Conductive Bed: Th...mentioning
confidence: 99%
“…Naturally, lab‐scale studies are rarely about the economics of an application, but a life cycle assessment would be one way of investigating at an early stage which technical modifications might have a realistic chance for scale‐up. These life cycle assessment studies have, e.g., been carried out for wastewater treatment processes (Mathuriya, Hiloidhari, Gware, Singh, & Pant, 2020 ; Peñacoba‐Antona et al, 2021 ) and provide information on the economic and ecological viability of the proposed processes. The same applies to the use of carbon or metal‐based materials as the basis for electrodes and to the question of which compounds used for optimization would be economically and ecologically viable.…”
Section: Future Direction Of Bes Performance Optim...mentioning
confidence: 99%